Comparison of the quality of B-scan ultrasound in modern high-end devices - Merkel, Daniel; Stahlheber, Hannah; Chupina, Victoria; Schneider, Christoph (Zeitschrift für Gastroenterologie, 2018)
Purpose The quality of an ultrasound device’s B-scan mode is decisive in obtaining clear and informative images. High demands are placed upon ultrasound devices, particularly in cases where evidence of small lesions of parenchymal organs is being gathered.Methods We tested the quality of the B-scan mode in ultrasound devices of 7 different manufacturers. We performed ultrasound examinations of 3 predefined abdominal sections on 4 healthy subjects with 7 different ultrasound devices. Documentation was compiled digitally by recording video sequences. Any characteristics identifying the manufacturer were removed. Subsequently, the sequences were organized into corresponding pairs. The resulting 252 video pairs were shown side by side to a panel of 10 experienced ultrasound examiners who evaluated the quality of the scans by way of direct visual comparison.Results Two of the 7 devices were clearly judged to be of higher quality. In part, the differences in the overall evaluation and within the subgroups reached levels of statistical significance. The ranking of the tested devices did not correlate with their suggested retail prices.Conclusion There are relevant differences in the quality of the B-scan mode of modern high-end devices. The suggested retail prices do not correlate with the B-scan quality of the ultrasound devices.
Keywords: B-Scan; device; comparison; sonography; quality; ultrasound